The influence of natural factors on the spatial distribution of aufeis in Ulaanbaatar, Mongolia - Ulambayar, Ganbold; Watanabe, Tatsuya; Dashtseren, Avirmed; Nakamura, Dai; Jambaljav, Yamkhin; Byambabayar, Ganbold; Temuujin, Khurelbaatar; Tsogt-Erdene, Gansukh; Otgonjargal, Dagvadorj (Frontiers in Earth Science, 2025)
Aufeis is a common phenomenon in the Northern Hemisphere and continues to pose a recurring challenge to settlement areas and urban infrastructure in Ulaanbaatar, Mongolia, during winter. Although it occurs annually, the processes and natural factors that contribute to its formation are not yet fully understood. This study analyzed the long-term spatial distribution of aufeis and the natural factors influencing its occurrence. Landsat satellite imagery from 2009 to 2024 was used to track multi-year changes in aufeis extent, and the results were compared with various natural factors. The findings revealed that the extent of aufeis over the past 14 years fluctuated between 0.01 km2 and 0.03 km2. It showed a weak correlation with air temperature but a relatively strong correlation with precipitation prior to aufeis formation. During the winter of 2023–2024, the aufeis expanded to 0.04 km2 and encroached into settlement areas. This shift was associated with a thick snow cover, which insulated the ground, prevented freezing, and allowed spring water to flow beneath the snowpack. The water subsequently accumulated in low-lying areas, leading to the formation of aufeis. These areas are densely populated, and as a result, many households were affected by the expansion of aufeis during the 2023–2024 winter. Additionally, surface emergence of soil water contributed to the enlargement of the aufeis. These results highlight the critical role of snow cover thickness, topography, and subsurface hydrology in controlling the extent and spatial dynamics of aufeis development.